SORPTION OF METAL IONS ON CLAY MINERALS. III. NUCLEATION AND EPITAXIAL GROWTH OF ZN PHYLLOSILICATE ON THE EDGES OF HECTORITE - Schlegel M.L.; Manceau A.; Charlet L.; Hazemann J.-L.; Chateigner D. (My University, 2001)
The impact of dissolved Si ([Si]aq) on Zn uptake in dilute suspensions (0.65 g/L) of hectorite was investigated at pH 7.30, a total Zn concentration (TotZn) of 520 μM, and ionic strength of 0.3 M (NaNO3 salt) by kinetics experiments and polarized extended X-ray absorption fine structure (P-EXAFS) spectroscopy.At low [Si]aq (∼30 to 60 μM), 5.8% of TotZn was adsorbed within the first 3 h of reaction. The sorption rate was lower afterwards, and Zn uptake amounted to 14.6% of TotZn after 168 h of reaction. These rates are consistent with Zn sorption on pH-dependent edge sites of hectorite platelets. At high [Si]aq (∼530 μM), a higher initial sorption rate was observed, the fraction of Zn removed amounting to 15.2% of TotZn at t = 3 h and 90.7% at t = 120 h. After 9 h of reaction time, Si uptake also occurred; the Si/Zn uptake ratio (1.09 ± 0.08) was between those of TO (∼0.67) and TOT (∼1.33) trioctahedral phyllosilicates, which suggests the neoformation of a Zn phyllosilicate. In the absence of hectorite, neither Zn nor Si were removed from solution, even at high [Si]aq, indicating that Zn uptake occurred by sorption on hectorite surface.Comparison of spectra for sorption samples and Zn references indicated that sorbed Zn was located in a clay-like structural environment. The angular dependence observed for all P-EXAFS spectra demonstrated that Zn cations are structurally attached to the edges of hectorite platelets. The size and structure of these Zn surface complexes varied with [Si]aq and reaction time. At low [Si]aq and after a long reaction time (t = 96 h), Zn was surrounded by in-plane 1.7 ± 0.6 Zn and 1.4 ± 0.3 Mg at 3.08 Å, and by out-of-plane 0.6 ± 1.1 Si at 3.28 Å. These results point to predominant formation of small polymers containing on average two to three Zn cations and located in structural continuity with the hectorite octahedral sheet. At high [Si]aq, higher numbers of Zn and Si and lower numbers of Mg neighbors were detected at t = 9 h; at t = 120 h, Zn was surrounded by in-plane 6.0 ± 0.4 Zn at 3.10 Å and by out-of-plane 3.6 ± 0.4 Si at 3.27 Å as in a Zn phyllosilicate. These results document for the first time the nucleation and epitaxial growth at ambient temperature of Zn phyllosilicate at the edges of smectite minerals under controlled laboratory conditions.